Multi-functional nanogel with cascade catalytic performance for treatment of diabetic oral mucosa ulcer - Zheng, Yanfen; Li, Zhiguo; Liu, Chuyi; Fan, Xiaotong; Luo, Zheng; Li, Zibiao; Wu, Yun-Long (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Diabetic oral mucosa ulcers face challenges of hypoxia, hyperglycemia and high oxidative stress, which result in delayed healing process. Oxygen is regarded as an important substance in cell proliferation, differentiation and migration, which is beneficial to ulcer recovery. Methods: This study developed a multi-functional GOx-CAT nanogel (GCN) system for the treatment of diabetic oral mucosa ulcers. The catalytic activity, ROS scavenge and oxygen supply ability of GCN was validated. The therapeutic effect of GCN was verified in the diabetic gingival ulcer model. Results: The results showed that the nanoscale GCN was capable of significantly eliminating intracellular ROS, increasing intracellular oxygen concentration and accelerating cell migration of human gingival fibroblasts, which could promote diabetic oral gingival ulcer healing in vivo by alleviating inflammation and promoting angiogenesis. Discussion: This multifunctional GCN with ROS depletion, continuous oxygen supply and good biocompatibility, which might provide a novel therapeutic strategy for effective treatment of diabetic oral mucosa ulcers.